Pola Hidup Sehat Selama Pandemi Covid-19 Pada kader PKK di Ciseeng Kabupaten Bogor - Diniwati Mukhtar; Linda Weni; Wan Nedra; M Arsyad; Yulia Suciati; Dita Safira (Lembaga Penelitian Universitas YARSI, 2020)
Changes in lifestyle and modernization have caused a shift in the pattern of diseases from communicable to non-communicable diseases (NCD). The NCD category includes diabetes, hypertension, obesity, coronary heart disease. Non-communicable diseases are a challenge during the Covid-19 pandemic because they are comorbid, which will aggravate the disease. Therefore it is necessary to educate on a healthy lifestyle to avoid these new infectious diseases. The method was carried out through webinars with the topic of an active lifestyle, teachings on faith and introduction to herbs to PKK cadres (Family Welfare Empowerment – FWE) in Ciseeng village. The metabolic health characteristics have normal values of 0%, 26%, 100%, 74% for waist circumference (WC), body mass index (BMI), systolic and diastolic blood pressure, respectively. Knowledge of healthy lifestyle from the webinar increased from 51.30% to 85.96% (p <0.05). The conclusion is that the metabolic health of respondents is considered at risk, while webinar activities reduce the risk of comorbidities.